A teratocarcinoma-like human embryonic stem cell (hESC) line and four hESC lines reveal potentially oncogenic genomic changes. - Outi Hovatta; Marisa Jaconi; Virpi Töhönen; Frédérique Béna; Stefania Gimelli; Alexis Bosman; Frida Holm; Stefan Wyder; Evgeny M Zdobnov; Olivier Irion; Peter W Andrews; Stylianos E Antonarakis; et al. (PLoS ONE)
The first Swiss human embryonic stem cell (hESC) line, CH-ES1, has shown features of a malignant cell line. It originated from the only single blastomere that survived cryopreservation of an embryo, and it more closely resembles teratocarcinoma lines than other hESC lines with respect to its abnormal karyotype and its formation of invasive tumors when injected into SCID mice. The aim of this study was to characterize the molecular basis of the oncogenicity of CH-ES1 cells, we looked for abnormal chromosomal copy number (by array Comparative Genomic Hybridization, aCGH) and single nucleotide polymorphisms (SNPs). To see how unique these changes were, we compared these results to data collected from the 2102Ep teratocarcinoma line and four hESC lines (H1, HS293, HS401 and SIVF-02) which displayed normal G-banding result. We identified genomic gains and losses in CH-ES1, including gains in areas containing several oncogenes. These features are similar to those observed in teratocarcinomas, and this explains the high malignancy. The CH-ES1 line was trisomic for chromosomes 1, 9, 12, 17, 19, 20 and X. Also the karyotypically (based on G-banding) normal hESC lines were also found to have several genomic changes that involved genes with known roles in cancer. The largest changes were found in the H1 line at passage number 56, when large 5 Mb duplications in chromosomes 1q32.2 and 22q12.2 were detected, but the losses and gains were seen already at passage 22. These changes found in the other lines highlight the importance of assessing the acquisition of genetic changes by hESCs before their use in regenerative medicine applications. They also point to the possibility that the acquisition of genetic changes by ESCs in culture may be used to explore certain aspects of the mechanisms regulating oncogenesis.